2018
DOI: 10.1002/jts.22257
|View full text |Cite
|
Sign up to set email alerts
|

Parent Discrepancies in Ratings of Child Behaviors Following Wartime Deployment

Abstract: Researchers have shown that parents often disagree in their ratings of their children's behavior, and that these discrepancies are typically related to child and family characteristics (e.g., child's age, parent psychopathology). Few studies, however, have examined discrepancies in how mothers and fathers rate child behavior during a stressful family context such as a parent's wartime deployment. The present study of 174 military families (children aged 6 to 11 years; 54.0% female) examined whether family fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The crossover via couple interaction explanation for crossover posits that a workers’ posttraumatic stress symptoms negatively influence their partners by harming the quality of their relationships (Westman, 2001). Studies have found negative relationships between military members’ PTSD symptoms and relationship quality (Allen et al, 2010; Bergmann et al, 2014; Chesmore et al, 2018; Knobloch-Fedders et al, 2017; Renshaw & Campbell, 2017). Other research has shown that experiencing harassment at work is associated with poorer marital adjustment (Dionisi & Barling, 2015), as are PTSD symptoms related to workplace accidents (Lameiras et al, 2018).…”
Section: Theoretical Framework: Stress and Strain Crossover Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The crossover via couple interaction explanation for crossover posits that a workers’ posttraumatic stress symptoms negatively influence their partners by harming the quality of their relationships (Westman, 2001). Studies have found negative relationships between military members’ PTSD symptoms and relationship quality (Allen et al, 2010; Bergmann et al, 2014; Chesmore et al, 2018; Knobloch-Fedders et al, 2017; Renshaw & Campbell, 2017). Other research has shown that experiencing harassment at work is associated with poorer marital adjustment (Dionisi & Barling, 2015), as are PTSD symptoms related to workplace accidents (Lameiras et al, 2018).…”
Section: Theoretical Framework: Stress and Strain Crossover Theorymentioning
confidence: 99%
“…In the workplace, traumatic stressors can involve threats of suffering, injury, or death to workers or those around them, and can also include severe forms of aggression such as bullying, sexual harassment, and violence. Within the military context, for instance, combat experiences are associated with PTSD symptoms and general distress (e.g., Allen et al, 2010; Chesmore et al, 2018; Snyder et al, 2016). Similarly, among police officers and firefighters, duty-related stressors (e.g., death encounters, physical threats, etc.)…”
Section: Theoretical Framework: Stress and Strain Crossover Theorymentioning
confidence: 99%
“…More supportive mothers may have a heightened awareness of their children's CSA experiences and symptoms, and some caregivers might overestimate their child's symptoms, whereas others could be more accurate. Alternatively, mothers' ratings of children's symptoms are driven by other factors, such as maternal levels of PTSS and depression (Chesmore et al, 2018;Scheeringa et al, 2015). Further, there are a variety of potential factors that drive children's reporting of symptoms, including metacognition, therapeutic rapport, and, perhaps, their beliefs regarding the implications of disclosing their symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of concordance are also evident for both trauma exposure (Goodman et al., 2010; Hungerford et al., 2010; Oransky et al., 2013; Stover et al., 2010) and trauma‐related symptoms (Dyb et al., 2003; Humphreys et al., 2017; Scheeringa et al., 2006; Wamser‐Nanney & Campbell, 2021). Caregivers tend to report lower rates of their children's trauma exposure relative to what their children report (Ceballo et al., 2001; Oransky et al., 2013; Stover et al., 2010). Agreement regarding trauma exposure may be complicated, as it may require children to disclose the details of their experiences, including all of the trauma types to which they have been exposed.…”
mentioning
confidence: 97%
See 1 more Smart Citation